PENINGKATAN KEAKTIFAN SISWA MELALUI PENERAPAN METODE DISCOVERY DALAM PEMBELAJARAN PKn DI KELAS X2 SMA NEGERI 2 LENGAYANG PESISIR SELATAN - Winda, Melda (TINGKAP, 2014)
This study aims to determine the increase in activity of students in the learning process of citizenship education by using the discovery method in classroom X2 SMAN 2 Lengayang, the District of Pesisir Selatan. The Class Action Research approach was used in this research. The subjects of this research were students of class X2 SMAN 2 Lengayang Pesisir Selatan District in the first semester of the school year 2012/2013. Data in this research were collected through observation and interview. The collected data were analyzed using qualitative and quantitative techniques. The findings of this study indicate that the application of the method of discovery in the citizenship education can increase the learning activity of students in the class X2 SMAN 2 Lengayang, the District of Pesisir Selatan. Key Words: Learning activity, civic education, discovery model